Association and Expression of Cluster of Differentiation 4 (CD4) Gene in IPB-D2 Chicken Related to Immunocompetence Index - D. Lestari; S. Murtini; N. Ulupi; A. Gunawan; C. Sumantri (Tropical Animal Science Journal, 2023)
The CD4 gene plays an important role in the immune process by producing CD4 molecules that aid in producing antibodies. IPB-D2 chickens are selected from IPB-D2 chickens based on IgY concentration and ND antibody titer. This study aimed to analyze the polymorphism of the CD4 gene, unravel the mRNA expression of CD4 gene in IPB-D2 chicken related to the immunocompetence index, and detect the CD4 gene pathway. The total samples used were 100 IPB-D2 G2 chickens aged 21 weeks. Blood samples were collected for ELISA test, HI test, sequencing test, and seca tonsil tissue for relative mRNA expression. Polymorphism and association data were analyzed using MEGAX, FinchTV, SNPstat, and DNAsp. The relative mRNA expression analysis was conducted using qRT-PCR. The pathway analysis of the CD4 gene was performed using the Kyoto Encyclopedia of Genes and Genome (KEGG) pathway analysis. The result showed there were 4 SNPs of the CD4 gene in IPB-D2 chicken, i.e., g.7526 C>T, g.7825 C>T, g.8100 C>A, and g.8157 T>A. All CD4 SNPSs showed no association with IgY concentration and ND antibody titers. Relative mRNA expression shows that IPB-D2 chickens with high ND antibody titers have a higher level of expression when compared to IPB-D2 chickens with low ND antibody titers. Furthermore, pathway analysis showed the CD4 gene involved in the T cell receptor (TcR) signaling process. This study concludes that the CD4 gene is polymorphic and involved in the T cell receptor signaling process. This study demonstrated that polymorphisms of the CD4 gene in IPB-D2 chicken might not contribute to the IgY concentration and ND antibody titer but can serve as a reference in the study of CD4 genes in the other chicken breeds related to the other immunocompetence index.